Ent-Dihydrotucumanoic acid promotes apoptosis in PC-3 human prostate cancer cells - Zhou, Min; Li, Weibing (Cellular and Molecular Biology, 2019)
Prostate cancer (PC) has become a disease that pose a serious threat to men’s health and life. In recent years, due to the changes of environment, lifestyle and other factors, the incidence of PC has been increasing rapidly in recent years, which is a serious threat to men’s health. Ent-Dihydrotucumanoic Acid (DTA) is a compound isolated from Asteraceae of gymnosperms, which has many pharmacological effects. The effect of DTA on the growth of tumor cell line was studied by CCK-8 method, mitochondrial membrane potential and apoptosis were detected by flow cytometry, apoptosis-related genes were detected by Western blot assay, and the absorptivity of Caspase-3 and Caspase-9 was measured by spectrophotometer. It was found that DTA induces apoptosis of human prostate cancer cell line PC3 through mitochondrial pathway, thus preventing the development of prostate cancer. It lays the experimental foundation for the further development of DTA.